2021
DOI: 10.31234/osf.io/z6kxm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Moral Values Predict County-Level COVID-19 Vaccination Rates in the United States

Abstract: Despite the widespread availability of COVID-19 vaccines, the United States has a depressed rate of vaccination as of September 2021. Understanding the psychology of collective vaccine refusal, particularly the sources of variation across U.S. sub-populations, can aid in designing effective intervention strategies to increase vaccination across different regions. Here, we demonstrate that county-level moral values (i.e., Care, Fairness, Loyalty, Authority, and Purity) are associated with COVID-19 vaccination r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…Over the past decade, research has found that endorsement of moral foundations can explain political differences on a variety of issues, including support for stem cell research (Clifford and Jerit, 2013), attitudes toward the poor (Low and Wui, 2015), willingness to act on climate change (Dickinson et al, 2016), blaming victims versus perpetrators of violence (Niemi and Young, 2016;LaPierre and Bruchmann, 2021), and willingness to befriend political outgroup members (Bruchmann et al, 2018). Additionally, relevant to the COVID-19 pandemic, research has found a link between endorsement of the purity foundation with vaccine hesitancy (Amin et al, 2017;Karimi-Malekabadi et al, 2021); this is likely due to the belief that a vaccine would compromise physical purity.…”
Section: Moral Foundations Predicts Perceptions Of Covid-19 Public He...mentioning
confidence: 99%
“…Over the past decade, research has found that endorsement of moral foundations can explain political differences on a variety of issues, including support for stem cell research (Clifford and Jerit, 2013), attitudes toward the poor (Low and Wui, 2015), willingness to act on climate change (Dickinson et al, 2016), blaming victims versus perpetrators of violence (Niemi and Young, 2016;LaPierre and Bruchmann, 2021), and willingness to befriend political outgroup members (Bruchmann et al, 2018). Additionally, relevant to the COVID-19 pandemic, research has found a link between endorsement of the purity foundation with vaccine hesitancy (Amin et al, 2017;Karimi-Malekabadi et al, 2021); this is likely due to the belief that a vaccine would compromise physical purity.…”
Section: Moral Foundations Predicts Perceptions Of Covid-19 Public He...mentioning
confidence: 99%
“…We would also like to acknowledge that the concept of moral purity, even though predictive of various real-world behaviors (e.g., Atari, Reimer, et al, 2022;Reimer et al, 2022), is complex and may be multifaceted (Gray et al, 2022). With that said, our work is a clear illustration for the value of a pluralist-descriptive approach to human morality -one that is not confined to normatively endorsed foundations in the West (Atari, Haidt, et al, 2022).…”
Section: Notementioning
confidence: 83%
“…MFT is a pluralistic, descriptive account of morality, which posits that (at least) five foundations -Care, Fairness, Loyalty (in-group), Authority, and Purity -have contributed to solving adaptive problems throughout humans' evolutionary past. In addition to a wide array of studies showing the predictive validity of MFT (e.g., Reimer et al, 2022), it has also been applied in various text analytic studies (e.g., Araque et al, 2020;Dehghani et al, 2014;Kennedy, Atari, Davani, Hoover, et al, 2021;Mokhberian et al, 2020) to study moral concerns as they manifest in various contexts (for a review, see . As such, it is a fitting framework for the study of the moral language of hate.…”
Section: Overview Of the Present Researchmentioning
confidence: 99%
“…Purity values can predispose people to negatively evaluate outgroup members who are perceived to be potential carriers of pathogens, subsequently justifying prejudicial or exclusive behaviors (e.g., hate crimes against outgroup members) or policies (e.g., imposing travel bans or deportations). In addition, recent research suggests that regional variation in Purity across U.S. counties is reliably associated with lower vaccination rates (Karimi-Malekabadi et al, 2021), which can be thought of as an ironic effect since Purity values may have culturally evolved to guard people against diseases, but the same values in contemporary settings seem to discourage vaccination, one of the most effective ways to combat communicable diseases at individual and population levels (Amin et al, 2017). This ironic effect may be attributable to the contemporary pandemic mismatch: while historically infectious diseases have been easily detectable (e.g., open sores), the cues to COVID-19 are limited due to asymptomatic and presymptomatic transmission of the disease (Ackerman et al, 2021), coupled with some politicians' rhetoric downplaying the threat of the disease (Calvillo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We then averaged these county-level conservatism estimates for the same periods as with our pathogen data (2000, 2004, 2008, 2012, 2016, and 2020 elections). This method for quantifying countylevel conservatism based on voting behavior has been previously used in Karimi-Malekabadi et al (2021).…”
Section: Methodsmentioning
confidence: 99%